Relawan dalam Perspektif Islam (Studi : Aksi Cepat Tanggap Cabang Sumatera Utara) - Ade Novita; Mardhiah Abbas; Endang Ekowati (UIN Sumatera Utara, 2021)
Humans are weak creatures who are powerless to face natural disasters, which have an impact on all aspects of life. Volunteers on this issue, present for humanity and natural disasters. Volunteers are the most needed fighters at the right time and on the front lines. The Humanitarian Foundation for Aksi Cepat Tanggap (ACT) is an organization whose members are called volunteers. ACT is spread across various regions in Indonesia, one of its branches is in Medan, namely Aksi Cepat Tanggap, North Sumatra Branch (ACT Sumut). The purpose of this study is to find out what is meant by volunteering from an Islamic perspective and to find out how the role of Aksi Cepat Tanggap’s North Sumatra Branch is as a humanitarian movement (volunteers). The method used is field research with a qualitative research approach. Sources of data were obtained from volunteers in ACT North Sumatra. The findings of the study found that Islam appeals to work and do good deeds outside the scope of profit and loss, namely voluntary work or volunteering who only expects the pleasure of Allah SWT. Volunteers are in line with what Islam teaches, for example in terms of helping. In conclusion, a volunteer in an Islamic perspective is a person or group of people who aim to help people who need humanitarian assistance voluntarily to include people who are in the way of Allah. ACT North Sumatra plays a role as a liaison between the beneficiary (donors and benefactors) to parties they cannot reach directly to provide humanitarian assistance to people in need.